River interlinking in India - "Singh , S . R. (ed.)" (New Delhi, 2006)
This book a path breaking volume packed with excellent theortical, concise, lucid comprehensive pieces and comparative case studies of river interlinking, with a collection of 28 research papers authored by eminent contributors. This book is shared on series analysis using up-to-date materials and data ,systematic, scientific and critical investigation of various pertinent issues of rivers interlinking in India which has been authored and edited by learned editors.
Keywords: Rivers-Interlinking